COMMON GROUND: THE PERSPECTIVES OF TIMOTHY L. SMITH ON AMERICAN RELIGIOUS HISTORY. - Cunningham, Floyd T. (Fides et historia, 2012)
The article focuses on the American evangelical scholar Timothy L. Smith and his viewpoints on American religious history. The author emphasizes that Smith appreciated both the religious diversity and the commonalities of the different faiths of people in the U.S., and that Smith believed that the core of American values was based upon the bible. The author discusses Smith's book ''Revivalism and Social Reform: American Protestantism on the Eve of the Civil War'' and its importance regarding the history of revivalism, American attitudes on social reform and conflicts among American churches.